2009
DOI: 10.1175/2009jcli2434.1
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Strong Northeast Asian Summer Monsoon

Abstract: The characteristics of a strong northeast Asian summer monsoon (NEASM) with and without (A and B type, respectively) a basinwide warming in the Indian Ocean during the preceding winter are examined for the period of 1979-2006. In the case of the A type, strong El Niñ o-like sea surface temperature (SST) decays very rapidly from the preceding winter (December-February) to the following summer (June-August), which may be due to a feedback process of the warm Indian Ocean. In addition, the A-type strong NEASM is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Fan et al (2013) emphasized the role of cooling SSTs in the central Pacific, rather than the eastern Pacific, in developing and maintaining the WNP anticyclonic anomaly. In addition, Kim et al (2009) also indicated that a strong East Asian summer monsoon and weak WNP monsoon can occur with and without a basinwide warming in the IO during the preceding winter. Whether quasi-biennial oscillations appear or not, however, depends on the location of cyclonic/ anticyclonic anomaly over the WNP and the persistence of ENSO.…”
Section: Introductionmentioning
confidence: 94%
“…Fan et al (2013) emphasized the role of cooling SSTs in the central Pacific, rather than the eastern Pacific, in developing and maintaining the WNP anticyclonic anomaly. In addition, Kim et al (2009) also indicated that a strong East Asian summer monsoon and weak WNP monsoon can occur with and without a basinwide warming in the IO during the preceding winter. Whether quasi-biennial oscillations appear or not, however, depends on the location of cyclonic/ anticyclonic anomaly over the WNP and the persistence of ENSO.…”
Section: Introductionmentioning
confidence: 94%
“…There are wide ranges of spatiotemporal factors that affect East Asian summer monsoon. For example, the variations in the sea surface temperature (SST) over the tropical Pacific, such as El Niño–Southern Oscillation (ENSO) [ Chang et al , ; Yim et al , ; Kim et al , ; Shin et al , ; Yun et al , ] and Indian Ocean [ Xie et al , ], as well as local ocean‐atmosphere feedback processes [ Lee et al , ; Xiang et al , ], affect the summer climate over East Asia. The atmospheric variations, such as the western Pacific subtropical high [ Lu and Dong , ; Yun et al , ], Okhotsk high [ Tachibana et al , ], and Pacific‐Japan atmospheric teleconnection pattern [ Nitta , ; Kosaka and Nakamura , ] also play a significant role in the East Asian summer climate.…”
Section: Introductionmentioning
confidence: 99%
“…At the interannual scale, the PJ pattern is related to ENSO, with a warm phase of ENSO in the preceding winter corresponding to a suppressed convection in summer over the WNP region [Nitta, 1987;Kosaka and Nakamura, 2010], indicating that the PJ pattern could be forced by the tropical variability. Extensive studies on the WNP-EA monsoon and WNPSH demonstrated that the lower tropospheric anomalous circulation over the WNP is largely forced by SST [Wang et al, 2001;Lu et al, 2006;Kim et al, 2009;Zhou et al, 2009aZhou et al, , 2009bPark et al, 2010;Zhou and Zou, 2010;He and Zhou, 2014]. Given the realistic tropical SST forcing by using a partially coupled model, a substantial amount of PJ variability can be captured [Ding et al, 2014].…”
Section: Introductionmentioning
confidence: 99%